Humanist, Pluralist, and Dialogical Concepts in Hindu Theology - Jyotis, Pradeep (International Journal of Multidisciplinary Sciences, 2023)
The aim of this research is to describe humanist, pluralist, and dialogical concepts in Hindu theology. The method used is qualitative with a descriptive approach. Human life cannot be separated from the beliefs he holds. These beliefs generally take the form of religion (organized religion). Outside of that, it is often called belief or original religion (native religion). Whatever the name, it all pivots on belief in the Almighty God, who is called by various names. This belief becomes the guidance of life for a person and their group. Religious teachings provide enlightenment and direction in life to their adherents. In living together in society, there are various religions and/or beliefs, and each religion or belief has differences, especially regarding faith (sraddha), the way to connect oneself to Him, and ethics. These differences give color and color to religious life in society. However, they have similarities in certain aspects, for example, regarding humanity.